2009
DOI: 10.1097/scs.0b013e318191d038
|View full text |Cite
|
Sign up to set email alerts
|

A Triage System for Referrals of Pediatric Skull Deformities

Abstract: The clinical pathways for craniosynostosis and nonsynostotic skull deformity are entirely different. At the Dutch Craniofacial Center (DCFC), all patients were assessed in the same multidisciplinary craniofacial clinic, a common practice in countries with developed health care. However, the high volume of referrals of nonsynostotic cases frequently resulted in the capacity of these clinics being exceeded, with some patients being assessed in the general pediatric plastic surgery clinic instead. In these genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…These data are from the Birmingham craniofacial center and could therefore well compare with the situation in the Netherlands. 1 , 2 For the situation in the Netherlands only the information from an article by Bredero-Boelhouwer is available, 3 in which 18 children were identified by the referrers as having craniosynostosis and in 14 of whom this diagnosis was confirmed in the tertiary center. Of the 89 referrals with the initial diagnosis nonsynostotic occipital plagiocephaly (NSOP) made by the referrer, 10 patients appeared to have a craniosynostosis.…”
Section: Referral and Diagnosticsmentioning
confidence: 99%
See 2 more Smart Citations
“…These data are from the Birmingham craniofacial center and could therefore well compare with the situation in the Netherlands. 1 , 2 For the situation in the Netherlands only the information from an article by Bredero-Boelhouwer is available, 3 in which 18 children were identified by the referrers as having craniosynostosis and in 14 of whom this diagnosis was confirmed in the tertiary center. Of the 89 referrals with the initial diagnosis nonsynostotic occipital plagiocephaly (NSOP) made by the referrer, 10 patients appeared to have a craniosynostosis.…”
Section: Referral and Diagnosticsmentioning
confidence: 99%
“…A craniosynostosis or positional skull deformity is primarily recognized by physical examination, notably skull shape 4 , 6 in combination with history taking, 3 , 5 and an imaging study is rarely indicated. 6 Both history taking and physical examination are well possible in the primary and secondary healthcare sectors.…”
Section: Referral and Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in many places throughout the world, access to a neurosurgeon is low, and responsibility for making the initial diagnosis rests with a family practitioner or pediatrician. 29 In this setting, imaging studies are essential. When imaging is key to the diagnosis, we suggest that CUS may become the first-line technique, avoiding routine use of radiography as an initial examination (Fig 8).…”
Section: Figurementioning
confidence: 99%
“…If a skull deformity is present, the physical examination and clinical history (key features described in the next subheads) are the most helpful and revealing pieces of information in the child's evaluation. A previous published anamnestic flowchart12 serves as a guideline to distinguish craniosynostosis from positional skull deformities. The key questions to differentiate the craniosynostoses from the nonsynostotic deformities are: (1) “Is deformity present at birth?” Craniosynostosis is present at birth, whereas nonsynostotic deformities develop in the neonatal period; (2) Is there a preferred sleep position?…”
Section: Methodsmentioning
confidence: 99%